2020
DOI: 10.3389/fnbot.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Spiking CPGs for Online Manipulation During Hexapod Walking

Abstract: Neural signals for locomotion are influenced both by the neural network architecture and sensory inputs coordinating and adapting the gait to the environment. Adaptation relies on the ability to change amplitude, frequency, and phase of the signals within the sensorimotor loop in response to external stimuli. However, in order to experiment with closed-loop control, we first need a better understanding of the dynamics of the system and how adaptation works. Based on insights from biology, we developed a spikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…The sCPG populations and MNP consist of 5 neurons each in order to produce a smooth, stable output with a minimum amount of neurons (Strohmer et al, 2020). The NSI is a single neuron so that all post-synaptic neurons connected to it receive the same inputs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sCPG populations and MNP consist of 5 neurons each in order to produce a smooth, stable output with a minimum amount of neurons (Strohmer et al, 2020). The NSI is a single neuron so that all post-synaptic neurons connected to it receive the same inputs.…”
Section: Methodsmentioning
confidence: 99%
“…Pure SNNs are also capable of manipulating output amplitude, frequency, and phase by updating differ-ent synaptic and neuronal characteristics (Strohmer et al, 2020). It was found that frequency could be changed by updating the value of the voltage threshold potential of the spiking central pattern generator (sCPG) neuron populations while amplitude was increased or decreased using the weight of the synap-tic conductance to the motor neuron population (MNP).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when the module state is toggled by outside stimuli, its behavior may appear superficially similar to bursting, but the underlying dynamics are fundamentally different [ 19 ]. This mechanism of rhythmogenesis is certainly not typical for biological central pattern generation [ 11 ], but it is effective from an engineering perspective.…”
Section: Building Blocks For Universal Computationmentioning
confidence: 99%
“…Instead, they simply provide contractile force in proportion to their depolarization [ 27 ]. The result is similar to applying an exponential low-pass filter to the spiking waveform [ 11 ], smoothing the output of the system so that changes occur only on the timescale of a few milliseconds, determined by the synaptic and membrane time constants.…”
Section: Building Blocks For Universal Computationmentioning
confidence: 99%
See 1 more Smart Citation